Where Have All the Normal Men and Women Gone? The Representation of Masculinity and Femininity in the Anti-Feminist Discourses of the Women’s Far Right Organisation Angry Mothers - Svatoňová, Eva (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Far-right social movements, whose popularity is on the rise in Europe, are often described as male-dominated organisations. Consequently, masculinity in the context of far-right organisations and the manosphere has received scholarly attention. However, most studies focus on male organisations and male leaders, giving the impression that “masculinist discourses” are reproduced only by men (Kimmel, 2013, 2018; Miller-Idriss, 2018). Yet, it becomes increasingly difficult to continue to ignore the patriarchal discourses of women engaged in activism in far-right organisations. Therefore, this exploratory study focuses on the construction of gender in the online communication of the Czech female organisation Angry Mothers. The study provides a deeper understanding of how women can co-construct the manosphere, which is deemed to be a fundamentally misogynist online space. To answer my research questions: How does the organisation use visual language to construct gender in their online communication? and What types of masculinity/femininity are portrayed as superior and what types of masculinity/femininity are portrayed as subordinate?, I analysed material published on the organisation’s Facebook page using the method of visual analysis (Rose, 2016), informed by Critical Discourse Analysis (CDA) (Wodak & Meyer, 2016). Based on the findings, I argue that the activists’ views presented in their political communication aim to preserve a masculinist, patriarchal structural order in society, despite their self-identification as protectors of women’s rights. However, through their discursive practices, they simultaneously portray women as powerful actors in their traditional gender roles.